SISTEM INFORMASI GEOGRAFIS PARIWISATA BERBASIS WEB MENGGUNAKAN REACT JS DI KABUPATEN SUBANG - Hermansyah Nur Ahmad; Jupriyanto Jupriyanto (Jurnal Teknologi Informasi Mura (JTI), 2026)
Subang Regency, West Java has significant natural and cultural tourism potential; however, tourism location information is not yet optimally integrated. Scattered information makes it difficult for tourists to obtain accurate location data, descriptions, and access to tourist destinations. This study aims to develop a web-based Geographic Information System (GIS) for tourism using React JS with a full-stack architecture. The system development applies the Agile method, enabling iterative and adaptive development based on user requirements. The system utilizes interactive digital maps based on Leaflet, search and category filtering features, multiple map display modes, and a review and rating feature without user login. The results show that the system provides accurate tourism location information, is easy to access, and offers real-time visit statistics. This system is expected to support regional tourism promotion and assist tourism management in data-driven decision-making.